FINANCIAL PROBLEMS AND MANAGEMENT OF COOPERATIVES (Third Sector Social Economic Review, 2017)
As it is the case in the whole world, the impact of cooperatives to the economy is relatively limited in our country, especially when they are widely considered as a financial and social development tool. The reason for the small share of the value that cooperatives produce in the total added value is the people's experience with many issues. One such example is the financial problem. Especially lack of automatic finance possibilities, hardships in contracting loans, their limited financial structures and high loan costs negatively affect cooperatives’ cooperation strength and prevent them to construct strong financial structures.The financial supply of cooperatives theoretically comes from two areas; self and foreign resources. For strengthening cooperatives and enabling them to solve their financial issues, it is essential to supply them a diversified foreign resource. Cooperatives are a must in achieving sustainable structural reforms and efficiency in all areas of Turkey. Everything must be done in order to strengthen cooperatives and enable them to overcome their financial issues and continue to exist in confidence. The financial burdens on top of cooperatives must be abolished. In this study, the cooperative banking system, its successful implementations and the sources that benefit cooperatives financially are investigated. Also, the financial measures that will enable cooperatives the ability to work in harsh conditions and carry them to the top spot that they deserve in the country's economy are discussed.
Keywords: Cooperative Financial Management; Cooperation; Financing; Financing Problems; Cooperative Banking.